The ability of SAMHD1 to block HIV-1 but not SIV requires expression of MxB - Buffone, Cindy; Kutzner, Juliane; Schaller, Torsten (Virology, 2019)
SAMHD1 is a human restriction factor known to prevent infection of macrophages, resting CD4+ T cells, and dendritic cells by HIV-1. To test the contribution of MxB to the ability of SAMHD1 to block HIV-1 infection, we created human THP-1 cell lines that were knocked out for expression of MxB, SAMHD1, or both. Interestingly, MxB depletion renders SAMHD1 ineffective against HIV-1 but not SIVmac. We observed similar results in human primary macrophages that were knockdown for the expression of MxB. To understand how MxB assists SAMHD1 restriction of HIV-1, we examined direct interaction between SAMHD1 and MxB in pull-down experiments. In addition, we investigated several properties of SAMHD1 in the absence of MxB expression, including subcellular localization, phosphorylation of the SAMHD1 residue T592, and dNTPs levels. These experiments showed that SAMHD1 restriction of HIV-1 requires expression of MxB.
Gesehen am 25.06.2020